Meet-in-the-middle attacks on FOX block cipher - IRong-jia L; INChen-hui J (Tongxin xuebao)
The security of the block cipher FOX against meet-in-the-middle attack was analyzed.Firstly,3-round meet-in-the-middle distinguishers was constructed and 6-round meet-in-the-middle attacks for FOX64 and FOX128 was proposed.The two attacks were beter attacks for 6-round FOX64 and FOX128,respectively.Secondly,the meet-in-the-middle distinguisher was extended of FOX128 to 4 rounds and proposed 7-round meet-in-the-middle attack combined with time/memory/data tradeoff.Compared to the currently known attacks on 7-round FOX128,The attack has a greater time and memory complexity,however the data complexity is much smaller.